2022
DOI: 10.1212/nxi.0000000000200035
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of MOG Antibodies in Children With Acquired Demyelinating Syndrome

Abstract: Background and ObjectiveThe spectrum of myelin oligodendrocyte glycoprotein (MOG) antibody–associated disorder (MOGAD) comprises monophasic diseases such as acute disseminated encephalomyelitis (ADEM), optic neuritis (ON), and transverse myelitis and relapsing courses of these presentations. Persistently high MOG antibodies (MOG immunoglobulin G [IgG]) are found in patients with a relapsing disease course. Prognostic factors to determine the clinical course of children with a first MOGAD are still lacking. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The lack of oligoclonal bands restricted to the CSF, the absence of periventricular lesions, variations in clinical symptoms, and the clinical evolution of ADEM are not in favor of Multiple Sclerosis (MS), although requiring a long follow-up for ruling out the dissemination in time which is the core characteristic of MS [ 58 ]. In addition, memory impairments, seizures, and psychiatric symptoms along with the presence of autoantibodies which are the typical manifestations of autoimmune encephalitis are not common features in ADEM [ 59 ]. The MOG antibody–associated disorder (MOGAD) consists of ADEM, transverse myelitis, and optic neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of oligoclonal bands restricted to the CSF, the absence of periventricular lesions, variations in clinical symptoms, and the clinical evolution of ADEM are not in favor of Multiple Sclerosis (MS), although requiring a long follow-up for ruling out the dissemination in time which is the core characteristic of MS [ 58 ]. In addition, memory impairments, seizures, and psychiatric symptoms along with the presence of autoantibodies which are the typical manifestations of autoimmune encephalitis are not common features in ADEM [ 59 ]. The MOG antibody–associated disorder (MOGAD) consists of ADEM, transverse myelitis, and optic neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pediatric MOGAD study of 116 children reported similar onset titers (median (interquartile range) = 1280 (640–5120) vs 1280 (640–5120), p = 0.291) in those with or without subsequent relapsing disease with a median follow-up of 3 years in the monophasic group. 5 In addition, analyzing follow-up samples on a research basis has improved our understanding of the dynamics of MOG-IgG serology but unfortunately the routine incorporation of follow-up MOG-IgG into clinical practice is premature. In 62 children with a median follow-up of 4 years, 14 relapsed.…”
mentioning
confidence: 99%
“…6 This pattern continues in adults where 22/38 (58%) of the monophasic patients had persistent MOG-IgG over a median of 17.5 months while 9/32 (28%) of the seroreverters relapsed. 7 The median time to relapse of 0.5–1 year 5,6 further limits the utility of MOG-IgG “persistence” in predicting a relapse. Finally, on terminology, seroreversion is a somewhat misleading term in the context of MOGAD where it frequently describes circulating MOG-IgG dropping below a cut-off rather than becoming undetectable.…”
mentioning
confidence: 99%
See 2 more Smart Citations